Dietary fatty acids modulate oxidative stress response to air pollution but not to infection - Ziegler, Ann-Kathrin; Jensen, Johan Kjellberg; Jiménez-Gallardo, Lucía; Rissler, Jenny; Gudmundsson, Anders; Nilsson, Jan-Åke; Isaksson, Caroline (Frontiers in Physiology, 2024)
Anthropogenic changes to the environment expose wildlife to many pollutants. Among these, tropospheric ozone is of global concern and a highly potent pro-oxidant. In addition, human activities include several other implications for wildlife, e.g., changed food availability and changed distribution of pathogens in cities. These co-occurring habitat changes may interact, thereby modulating the physiological responses and costs related to anthropogenic change. For instance, many food items associated with humans (e.g., food waste and feeders for wild birds) contain relatively more ω6-than ω3-polyunsaturated fatty acids (PUFAs). Metabolites derived from ω6-PUFAs can enhance inflammation and oxidative stress towards a stimulus, whereas the opposite response is linked to ω3-derived metabolites. Hence, we hypothesized that differential intake of ω6-and ω3-PUFAs modulates the oxidative stress state of birds and thereby affects the responses towards pro-oxidants. To test this, we manipulated dietary ω6:ω3 ratios and ozone levels in a full-factorial experiment using captive zebra finches (Taeniopygia guttata). Additionally, we simulated an infection, thereby also triggering the immune system’s adaptive pro-oxidant release (i.e., oxidative burst), by injecting lipopolysaccharide. Under normal air conditions, the ω3-diet birds had a lower antioxidant ratio (GSH/GSSG ratio) compared to the ω6-diet birds. When exposed to ozone, however, the diet effect disappeared. Instead, ozone exposure overall reduced the total concentration of the key antioxidant glutathione (tGSH). Moreover, the birds on the ω6-rich diet had an overall higher antioxidant capacity (OXY) compared to birds fed a ω3-rich diet. Interestingly, only the immune challenge increased oxidative damage, suggesting the oxidative burst of the immune system overrides the other pro-oxidative processes, including diet. Taken together, our results show that ozone, dietary PUFAs, and infection all affect the redox-system, but in different ways, suggesting that the underlying responses are decoupled despite that they all increase pro-oxidant exposure or generation. Despite lack of apparent cumulative effect in the independent biomarkers, the combined single effects could together reduce overall cellular functioning and efficiency over time in wild birds exposed to pathogens, ozone, and anthropogenic food sources.